Ekofeminisme dalam Anime Miyori no Mori Karya Nizou Yamamoto - I Gusti Ayu Sugiartini Mahardika; Silvia Damayanti; Ni Made Andry Anita Dewi (KIRYOKU, 2022)
This research is entitled "Ecofeminism in The Anime Miyori no Mori by Nizou Yumamoto". The purpose of this research is to examine the efforts of women in preserving the environment in the anime Miyori no Mori by Nizou Yumamoto. The methods used in this research were the literature study method and the informal method. This research used the theory of ecofeminism and semiotic proposed by Danesi to analyze the data that has been collected. The results of this research indicates there were several efforts made by women, namely the environmental care movement in the form of loving and preserving living things, supporting forest conservation in Komori Village. Aside from that, women also participated on environmental issue and fought the capitalism party by advocated and socialized the conservation as well as stated to anticipate and refused the project of the dam construction. Women used their sensitivity to the environment a lot to strive for sustainability, which is reflected in this anime.